ANALYSIS OF FINANCING STRUCTURE OF SEA FISHERMAN BUSINESS (DUANO TRIBE) IN TANJUNG PASIR VILLAGE, INDRAGIRI HILIR - Lamun Bathara; Chicka Willy Yanti; Rindi Metalisa (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Fishery business is one of the fisheries and marine sub-sectors where this business requires relatively large capital. Fishermen financing is still an obstacle in developing fishery businesses, especially small-scale capture fisheries carried out by marine tribal fishermen because the catch and capital are considered unstable. For this reason, there is a need for research to find out what the structure of business financing carried out by marine tribal fishermen is like. The purpose of this study was to analyze the investment, financing structure and financial feasibility of the sea tribe fisherman's business. The method used to analyze the data in this study is a quantitative descriptive method with a sample of 54 people. From the results of data analysis, it is known that the average investment is Rp. 14,325,674, -/ year. The average cost incurred in this business is Rp. 43,600,949/year, with an average income of Rp. 89,345,580/year and a profit of Rp 45,744,631/year. The R/C ratio value of 2.04 means that the business is feasible to continue where every additional Rp. 1, - will provide a profit of Rp. 2.04. The ROI value of 3.19 means that the business is feasible to continue, PP 0.31 means that the investment can return within a period of 0.31 years (fast return category), and NPV IDR 42,952,705 has a positive value, meaning that the business is feasible to continue.